P01.101 Treatment and survival of patients with lower grade glioma according to the 2007 and the 2016 WHO classification: A retrospective analysis of 423 patients. (19th September 2018) - Steidl, E; Zeiner, P; Wagner, M; Fokas, E; Forster, M; Ronellenfitsch, M; Steinbach, J P; Harter, P N; Bähr, O
Abstract: Background: Classification as well as treatment of patients with lower grade gliomas (°II+°III) have changed fundamentally during the last years. Molecular markers have augmented diagnostic workup and combined radiochemotherapy was established for most of the subgroups. However, molecular markers have not been part of the inclusion criteria of most of the relevant clinical trials. Larger analyses outside of clinical trials are rare. Material and Methods: We screened our clinical cancer database for patients with lower grade glioma newly diagnosed from 1995 to 2015. We identified 774 patients of whom 345 had to be excluded, resulting in an evaluable cohort of 423 patients. We evaluated general characteristics, morphological diagnosis, molecular markers, treatment, time-to-treatment-failure (TTF; initiation of a new treatment or death) and overall survival (OS). Results: According to the 2007 WHO classification our cohort included 145 (34.3%) Astrocytoma WHO °II, 56 (13.3%) Oligoastrocytoma/Oligodendroglioma WHO °II, 129 (52.5%) Astrocytoma WHO °III and 93 (22.0%) Oligoastrocytoma/Oligodendroglioma WHO °III. In 235 patients we were able to molecularly classify the tumors based on the 2017 WHO classification using IDH status and 1p/19q or ATRX status. Patients with a molecularly defined Oligodendroglioma showed a median TTF of 5.2, 4.2 and 7.8 years for radiotherapy, chemotherapy and radiochemotherapy, respectively. Patients with a molecularly defined Astrocytoma showed a median TTF of 1.6, 2.9 and 6.7 years for radiotherapy, chemotherapy and radiochemotherapy, respectively. In IDH wildtype tumors TTF was below 12 months without relevant differences. Treatment with combined radiochemotherapy resulted in markedly improve TTF in molecular defined oligodendroglioma and astrocytoma compared with either radiotherapy or chemotherapy alone. Due to the short follow-up of 5.3 years (mean) median OS has not been reached for any of the IDH mutant subgroups. Conclusion: Combined treatment with radiotherapy and chemotherapy resulted in markedly improved TTF in patients with molecularly defined oligodendroglioma and astrocytoma.